2019
DOI: 10.1371/journal.pntd.0007536
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating diversity in the class composition of the minicircle hypervariable region of Trypanosoma cruzi: New perspectives on typing and kDNA inheritance

Abstract: Background Trypanosoma cruzi , the protozoan causative of Chagas disease, is classified into six main Discrete Typing Units (DTUs): TcI-TcVI. This parasite has around 10 5 copies of the minicircle hypervariable region (mHVR) in their kinetoplastic DNA (kDNA). The genetic diversity of the mHVR is virtually unknown. However, cross-hybridization assays using mHVRs showed hybridization only between isolates belonging to the same genetic group. Nowadays there i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 70 publications
1
27
0
Order By: Relevance
“…Recently, we studied the hypervariable region of the minicircles (mHVR) by deep sequencing and observed that TcV and TcVI share minicircles with both parental DTUs (TcII as TcIII) and not just with TcIII, as observed in maxicircles. Based on these results we proposed that minicircle inheritance may be biparental in natural occurring hybrids [33]. Biparental inheritance of the kDNA has also been proposed for T. brucei [34][35][36].…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…Recently, we studied the hypervariable region of the minicircles (mHVR) by deep sequencing and observed that TcV and TcVI share minicircles with both parental DTUs (TcII as TcIII) and not just with TcIII, as observed in maxicircles. Based on these results we proposed that minicircle inheritance may be biparental in natural occurring hybrids [33]. Biparental inheritance of the kDNA has also been proposed for T. brucei [34][35][36].…”
Section: Introductionmentioning
confidence: 84%
“…The mHVRs for TEDa2cl4 were amplified according to the protocol and primers proposed in [33]. Amplicons were then purified using the magnetic beads Agencourt AMPure XP-PCR Purification (Beckman Genomics, USA).…”
Section: Mhvr Sequencingmentioning
confidence: 99%
See 2 more Smart Citations
“…The mitochondrial minicircles were inherited from both parental species, a phenomenon that has only been described sporadically in Trypanosomatids 5456 . In contrast, the mitochondrial maxicircles demonstrated clear and consistent uniparental inheritance from the L. braziliensis parent.…”
Section: Discussionmentioning
confidence: 99%